Effects of dietary D-lactate levels on rumen fermentation, microflora and metabolomics of beef cattle - Gao, Qian; He, Jianfu; Wang, Jin; Yan, Yonghui; Liu, Lei; Wang, Zuo; Shen, Weijun; Wan, Fachun (Frontiers in Microbiology, 2024)
Introduction Excessive intake of lactate caused by improper use of silage in animal husbandry has adverse effects on rumen fermentation, such as rumen acidosis. The speed of absorption and metabolism of D-lactate in rumen epithelial cells was slower than that of L-lactate, making D-lactate more prone to accumulate and induce rumen acidosis. Therefore, this study was conducted to explore the effects of dietary D-lactate levels on rumen fermentation of beef cattle and its mechanism in an in vitro system. Methods This experiment was adopted in single-factor random trial design, with 5 days for adaptation and 3 days for sample collection. Three treatments (n = 8/treatment) were used: (1) D-LA (0.3%), basal fermentation substrate with 0.3% (dry matter, DM basis) D-lactate; (2) D-LA (0.75%), basal fermentation substrate with 0.75% (DM basis) D-lactate; and (3) D-LA (1.2%), basal fermentation substrate with 1.2% (DM basis) D-lactate. Results With the dietary D-lactate levels increased, the daily production of total gas, hydrogen and methane, as well as the ruminal concentrations of acetate, propionate, butyrate, isobutyrate, valerate, isovalerate, total volatile fatty acid and D-lactate increased (p < 0.05), but the ruminal pH and acetate/propionate ratios decreased (p < 0.05). Principle coordinate analysis based on Bray-Curtis distance showed that increasing dietary D-lactate levels could significantly affect the structure of rumen bacterial community (p < 0.05), but had no significant effect on the structure of rumen eukaryotic community (p > 0.05). NK4A214_group, Ruminococcus_gauvreauii_group, Eubacterium_oxidoreducens_group, Escherichia-Shigella, Marvinbryantia and Entodinium were enriched in D-LA (1.2%) group (p < 0.05), as well as WCHB1-41, vadinBE97, Clostridium_sensu_stricto_1, Anaeroplasma and Ruminococcus were enriched in D-LA (0.3%) group (p < 0.05). Changes in the composition of ruminal microorganisms affected rumen metabolism, mainly focus on the biosynthesis of glycosaminoglycans (p < 0.05). Discussion Overall, feeding whole-plant corn silage with high D-lactate content could not induce rumen acidosis, and the metabolization of dietary D-lactate into volatile fatty acids increased the energy supply of beef cattle. However, it also increased the ruminal CH4 emissions and the relative abundance of opportunistic pathogen Escherichia-Shigella in beef cattle. The relative abundance of Verrucomicrobiota and Escherichia-Shigella may be influenced by glycosaminoglycans, reflecting the interaction between rumen microorganisms and metabolites.